2011
DOI: 10.1002/nme.3181
|View full text |Cite
|
Sign up to set email alerts
|

The meshless Galerkin boundary node method for Stokes problems in three dimensions

Abstract: SUMMARYThe Galerkin boundary node method (GBNM) is a boundary only meshless method that combines an equivalent variational formulation of boundary integral equations for governing equations and the moving least-squares (MLS) approximations for generating the trial and test functions. In this approach, boundary conditions can be implemented directly and easily despite of the fact that the MLS shape functions lack the delta function property. Besides, the resulting formulation inherits the symmetry and positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Since the nodes lie on Γ in the present method, the point interpolation is only needed on Γ. As in [10,[18][19][20], it is assumed that the boundary Γ is the union of piecewise smooth segments Γ ( = 1, 2, . .…”
Section: Boundary Variables Interpolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the nodes lie on Γ in the present method, the point interpolation is only needed on Γ. As in [10,[18][19][20], it is assumed that the boundary Γ is the union of piecewise smooth segments Γ ( = 1, 2, . .…”
Section: Boundary Variables Interpolationmentioning
confidence: 99%
“…To carry out integrations numerically, the boundary Γ is discretized into cells. It has been shown that one node per cell and the position of the node at the center of the cell can yield excellent results [15,18,19]. This nodal placement is used in this research.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Error estimation for meshless method is certainly important to increase the reliability and reduce the cost of numerical computations in many engineering problems. Some error analyses have been done for the MLS approximation and the meshless method based on it [69][70][71][72][73][74]. Krysl and Belytschko studied the convergence of the continuous and discontinuous shape functions of the second-order elliptic partial differential equations [75].…”
Section: Introductionmentioning
confidence: 99%
“…Another salient feature of the GBNM is the conservation of the symmetry and positive definiteness of variational problems in the process of numerical implementation. The GBNM has been successfully applied to problems in potential theory [11,31,32], linear elasticity [33] and fluid mechanics [34][35][36]. The corresponding convergence analysis and a priori error estimate have also been established.…”
Section: Introductionmentioning
confidence: 99%